1992
DOI: 10.21000/jasmr92010068
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acid/Base Accounting Techniques Used in Surface-Mine Reclamation

Abstract: Abstract. Surface mine reclamation laws in Texas permit the use of mixed overburden as a topsoil substitute. Overburden material must have a positive acid/base account (ABa) to remain within 4 feet of the reclaimed surface. Acid/base account is calculated by subtracting potential acidity (PA) plus exchangeable acidity (EA) from the inherent acid neutralization potential (NP) of the material. Material with a negative ABa may be limed to increase the AB a value. Two separate research studies were conducted to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Neutralization potential measures easily weatherable minerals (i.e., olivine and micas), including carbonates, present in an overburden (Doolittle et al, 1992). The NP of an overburden is determined using USEPA Method 600/2‐78‐054 3.2.3 (Sobek et al, 1978).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Neutralization potential measures easily weatherable minerals (i.e., olivine and micas), including carbonates, present in an overburden (Doolittle et al, 1992). The NP of an overburden is determined using USEPA Method 600/2‐78‐054 3.2.3 (Sobek et al, 1978).…”
mentioning
confidence: 99%
“…Siderite affects NP because Fe 2+ released during acid digestion does not undergo complete oxidation and hydrolysis (Eq. [4] and [5]) during NP evaluation (Doolittle et al, 1992; O'Shay et al, 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Đối với các mỏ khoáng sản mà trong thành phần quặng hoặc đất đá vây quanh có chứa các khoáng vật sulfid (ví dụ pyrit), chẳng hạn như vàng, Pb-Zn và một số loại khoáng sản khác, khả năng tạo dòng thải axit mỏ là rất lớn (Doolittle, et al, 1992; Global Acid Rock Drainage Guide). Đơn cử như trường hợp mỏ vàng Đắk Ripen ở Kon Tum.…”
Section: Dòng Thải Axit Mỏ Và ô Nhiễm Kim Loại Nặngunclassified
“…However, continued weathering of FeC0 3 produces a neutral to slightly acidic solution. Doolittle et al (1992) concluded that FeC0 3 affected NP because the Fe 2 + did not undergo complete oxidation and hydrolysis.…”
Section: Introductionmentioning
confidence: 99%